Handbook on cyber hate: the modern cyber evil - Wagner, Anne; Marusek, Sarah (Law and visual jurisprudence, 2024)
Navigating the Murky Waters of Modern Cyber Evil -- Part I. Theoretical Explorations of Modern Cyber Evil -- On Cyber-Envy -- Cyberhate. On shaping the public agenda by assembling contentious issues -- Reclaiming Moderation: Towards a Model of Moderated Counterspeech in the Digital Public Sphere -- Cyberhate: Medium? Message? Speech? Act? An Exploration -- Hate speech anthropologies. Evil, democracy, and social media: between Popper and Girard -- CYBERHATE FROM REASON TO EMOTIONS - Influencers and the Colombian Virtual Agora -- Cyber Hate Speech Detection and Analysis – An Evidence-based Forensic Linguistics Approach -- Between Freedom of Speech and Hate Speech: Similarities between Stages of Genocide and Aggression in Modern Media -- Rethinking hate speech and cyberhate concepts: The case of smear campaigns against judges in Poland -- Part II. Legal Perspectives on Modern Cyber Evil -- Legal-Linguistic Typology of Hate Speech as a Matrix for its Legal Regulation -- The legal categorisation of cyber hate: a corpus-assisted exploration of prompting, inciting, insulting and making contemptuous in hate speech discourse -- Bringing cyber-hate under control through a pro-active legal approach: an Australian case study -- Social Media and Online Trolling: Examining the Legal Developments in Platform Responsibilities for Tackling Trolling in the US, UK, and Australia -- Online Hate Speech under International Law -- “…a matter of grave concern”: Online hate speech in Ireland at the intersection of legislation and case law -- Different Facets of Cyber-hate in Russia and Controversial Legal Responses -- Online Discrimination Based on COVID-19: A Language and Law Perspective -- A Comparative Analysis of Anti-Cyberbullying Laws between Russia and China -- Part III. Cyber Evil in Society and Popular Culture -- The crime of fat shaming: between cyber bullying and racism -- Cyberbullying Movies: The Relevance of the Cinematic Portrayal of Cyberbullying -- Countering the Cyber-evil Narrative on Racism; Cultural Representation and The Potential Good of Cyberspace -- Textual and Non-Verbal Expressions of Cyberhate in South African Social Media Misconduct Dismissals -- Abuse of Rhizomatic Internet Memes: Disruptive Non-Verbal Discourse -- Aggressive E-Communication Among Teenagers: A Field Study -- Hegemonic Masculinity and beyond: an overview of social science and interdisciplinary research on the manosphere.